2002
DOI: 10.1097/00129689-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laparoscopic Colectomy With and Without the Aid of a Robotic Camera Holder

Abstract: The use of a robotic camera holder (AESOP 3000; Computer Motion, Inc., Santa Barbara, CA, U.S.A.) during laparoscopic surgery is slowly becoming more popular with laparoscopic surgeons. However, few published reports document the effects of the robot on operative outcomes or operative times. In the current study, we compared the use of a voice-controlled robotic camera holder to a human camera holder in a series of laparoscopic colectomies. The outcome data measured included the number of patients with postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Although not definitively proven, poor LCN performance may have a negative impact on surgeon performance, prolonging operative times. To overcome these problems, some surgeons have used robotic LCN systems with good results [2,18,20,21]. However, as compared with an experienced human camera operator, robotic systems have not demonstrated improvement in surgeon performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not definitively proven, poor LCN performance may have a negative impact on surgeon performance, prolonging operative times. To overcome these problems, some surgeons have used robotic LCN systems with good results [2,18,20,21]. However, as compared with an experienced human camera operator, robotic systems have not demonstrated improvement in surgeon performance.…”
Section: Discussionmentioning
confidence: 99%
“…Because interrater reliability of this method had not been established, we used a single blinded rater to minimize the possibility of consistency problems. Finally, as other studies have done [2,14,[18][19][20], we recorded procedure time, which, although limited in terms of directly reflecting LCN skill, may have shed some light on the effect of LCN skill on surgeon performance.…”
Section: Discussionmentioning
confidence: 99%
“…9 View of a laparoscopic distal gastrectomy. Two surgeons performed the operation via one camera port and four working ports for maintaining a stable view and are being widely used [1,5]. However, such robotic systems continue to have several problems and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…These merits have been ascertained in various types of surgery [1][2][3][4][5][6]. However, several problems have been noted.…”
mentioning
confidence: 99%
“…They react to the voice, to head motion signals, or to a joystick positioned on the left-hand side of the instrument. Merola et al [24] reported that there was less smudging, fogging, and inadvertent movements of the laparoscope when it was controlled by a robotic system. Also, Takahashi et al [16] examined 25 cases of laparoscopic inguinal hernia repair with ViKY and reported its benefits.…”
Section: Studymentioning
confidence: 99%